Sensitivity and responses of diatoms to climate warming in lakes heavily influenced by humans. (28th April 2014) - Berthon, Vincent; Alric, Benjamin; Rimet, Frédéric; Perga, Marie‐Elodie
Summary Diatom communities have been shown to respond strongly to current climate warming in remote lakes, while evidence remains equivocal for lakes under strong local human pressures. Temporal dynamics of planktonic diatoms in three subalpine lakes (Geneva, Annecy and Bourget) reconstructed from palaeolimnological approaches were used to assess the relative effects of phosphorus concentrations, fisheries management practices and climate warming in structuring communities over the last century. Changes in total phosphorous concentration (TP), air temperature and fish predation pressure could explain the temporal dynamics of most diatom species in the sediment records. TP was found to be not only the main driver of changes in community composition but also an important factor modulating diatom sensitivity and responses to climate warming. The diatom community of Lake Bourget showed the highest vulnerability and direct responses to climate warming, favouring spring species that can resist earlier stratification in mesotrophic lakes (such as Asterionella formosa, Aulacoseira islandica and Stephanodiscus parvus) and summer species that can make the best trade‐off between decreasing nutrient concentrations and increased water column stability (Diatoma tenuis, A. islandica). In Lake Geneva, climate warming also contributed to shaping diatom communities but through an indirect pathway; fisheries management practices and climate warming interacted to reinforce top‐down control, favouring large, colonial inedible species (Stephanodicus binderanus and A. formosa). For Lake Annecy, the most nutrient limited of the three lakes studied, no changes in diatom community structure were directly related to warmer air temperatures over the last 25 years. All three lakes have been subjected to the same climate variability. Yet the magnitude and responses of their diatom communities to climate warming were dissimilar and strongly modulated by differences in lake trophic status and fish management practices.